Canadian Practice Assessment in Chronic Obstructive Pulmonary Disease: Respiratory Specialist Physician Perception Versus Patient Reality - Paul Hernandez; Meyer S Balter; Jean Bourbeau; Charles K Chan; Darcy D Marciniuk; Shannon L Walker (Canadian Respiratory Journal)
INTRODUCTION: Chronic obstructive pulmonary disease (COPD) is a common respiratory condition and the fourth leading cause of death in Canada. Optimal COPD management requires patients to participate in their care and physician knowledge of patients’ perceptions of their disease.